Analisis mobilitas tenaga kerja pada sektor informal - Gusmawarni Astrid Handayani; Priyagus Priyagus; Siti Amalia (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
This research are probability mobility labor informal sector influenced by age, labor informal sector young age choose not to survive work on the informal sector, while of working age relatively productive choose to survive work on the informal sector. The probability of mobility labor informal sector affected by the level of education, labor informal sector with higher education choose not to survive work on the informal sector, while labor informal sector with low levels of education choose to stay work on the informal sector. The probability of mobility labor informal sector influenced by income, labor informal sector with high income choose to survive work on the informal sector, while labor informal sector with low incomes choose not to survive work on the informal sector. The probability of mobility labor informal sector not affected by gender, there is no difference between labor informal sector men and women in choosing to endure work on informal sector and not remain work on the informal sector.